Evolution of Earnings Management Practices in Public Companies - Judijanto, Loso; Majid, Jamaluddin; Wijayanti, Indah Oktari; Munir, Muhammad Syahrul; Sudiana, Urip (Westscience Press, 2024)
This bibliometric analysis explores the extensive body of literature on earnings management, highlighting its evolution and the current state of research globally. Utilizing data extracted from Scopus and analyzed through VOSviewer, this study maps out the interconnected themes and identifies significant contributions from various countries, with a focus on the role of corporate governance, audit quality, and financial reporting standards. The analysis reveals a growth in research volume over the years, reflecting increasing complexity and relevance. Key trends indicate a shift from traditional theoretical frameworks to more practical concerns, such as the implications of earnings management on financial stability and market perception. The study also underscores the importance of international collaboration and the impact of regulatory environments on earnings management practices. Findings from this study suggest directions for future research, emphasizing the need for advanced detection techniques and a deeper understanding of cross-cultural dynamics in earnings management.